ANALISIS KEPATUHAN PEKERJA DENGAN KEJADIAN KECELAKAAN KERJA PADA PT.X TAHUN 2019 - Devi Charolina Sanur; Tjipto Suwandi; Muhamadiah Muhamadiah (STIKes Al-Insyirah Pekanbaru, 2020)
The frequent occurrence of near miss is found such as being pinched, sprained and so on due to lack of following the SOP and not using PPE at PT. X. This study aims to analyze the relationship between age, years of service, compliance with SOP and compliance with the use of PPE on workers at PT. X in 2019. This type of research is quantitative with the type of analytic cross sectional study design. The sample in this study was 34 people. Data analysis was performed univariate, bivariate and multivariate. The results of research variables related to work accidents are age (p value = 0.020), years of service (p value = 0.042), adherence to follow SOP (p value = 0.024) and compliance with PPE use (p value = 0.002). The most dominant variable to work accidents is compliance with PPE use (p value = 0.002). Confounding variables are variables of age, years of service and compliance following the SOP. The conclusion in this study is adherence to the use of PPE as the most dominant factor for workplace accidents in workers at PT. X. It is recommended to PT. X to conduct a socialization about the use and danger of not using PPE as well as occupational safety and health.